Conjunctive and exclusive use of shallow groundwater for irrigation of spring wheat - McCormick, C. K., author; Guitjens, J. C., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 1998)
The use of drainwater for irrigation is a viable technology both for improving overall irrigation efficiency and for protecting water quality by reducing the mass output of salts and trace elements from irrigated areas. This was demonstrated in a field study at NewIands Agricultural Research Center in Fallon, NY by growing spring wheat (Triticum aestivum) under four irrigation water treatments. The four treatments were: 1) the exclusive use of canal water applied during the day; 2) the exclusive use of drainwater applied during the day; 3) the exclusive use of drainwater applied during the night; and 4) the conjunctive use of drainwater and canal water beginning with a day-time application of drainwater and finishing with canal water. The drainwater came from a shallow aquifer which had elevated levels of salinity and boron. The effects on crop yield of boron and salts applied with drainwater treatments were of primary interest. The field was divided into four blocks representing different soil conditions. Each block was divided into four plots and each plot was randomly assigned one of the four treatments. The growth response to these water qualities was evaluated by weighing plant samples harvested four times during the growing season. The hypothesis that daytime irrigation with drainwater would significantly reduce growth of spring wheat was rejected. The use of drainwater for irrigation appears technically feasible and offers opportunities for improving irrigation efficiency and for reducing the mass output of salts and trace elements from the Newlands Project.
USCID 14th technical conference
Not digitized by CSUL Digital Services.
Presented at Contemporary challenges for irrigation and drainage: proceedings from the USCID 14th technical conference on irrigation, drainage and flood control held on June 3-6, 1998 in Phoenix, Arizona.